Fast and Simple Protocol for N-Glycome Analysis of Human Blood Plasma Proteome - Denis E. Maslov; Anna N. Timoshchuk; Alexander A. Bondar; Maxim P. Golubev; Anna G. Soplenkova; Maja Hanic; Sodbo Z. Sharapov; Olga N. Leonova; Yurii S. Aulchenko; Tatiana S. Golubeva (Biomolecules)
N-glycome analysis of individual proteins and tissues is crucial for fundamental and applied biomedical research and medical diagnosis and plays an important role in the evaluation of the quality of biopharmaceutical and biotechnological products. The interest in this research area continues to grow annually, thereby increasing the demand for the high-throughput profiling of human blood plasma N-glycome. In response to this need, we have developed an optimized, simple, and rapid protocol for the N-glycome profiling of human plasma proteins. This protocol encompasses the entire analysis cycle, from plasma isolation to N-glycan spectrum quantification. While the proposed method may have lower efficiency compared to already published high-throughput methods, its adaptability makes it suitable for implementation in virtually any molecular biological laboratory.